The novel RAGE interactor PRAK is associated with autophagy signaling in Alzheimer's disease pathogenesis. Issue 1 (December 2016) - Kim, Yoonhee; Kim, Chaeyoung; Son, Sung; Song, Hyundong; Hong, Hyun; Han, Sun-ho; Mook-Jung, Inhee
Abstract Background The receptor for advanced glycation end products (RAGE) has been found to interact with amyloid β (Aβ). Although RAGE does not have any kinase motifs in its cytosolic domain, the interaction between RAGE and Aβ triggers multiple cellular signaling involved in Alzheimer's disease (AD). However, the mechanism of signal transduction by RAGE remains still unknown. Therefore, identifying binding proteins of RAGE may provide novel therapeutic targets for AD. Results In this study, we identified p38-regulated/activated protein kinase (PRAK) as a novel RAGE interacting molecule. To investigate the effect of Aβ on PRAK mediated RAGE signaling pathway, we treated SH-SY5Y cells with monomeric form of Aβ. We demonstrated that Aβ significantly increased the phosphorylation of PRAK as well as the interaction between PRAK and RAGE. We showed that knockdown of PRAK rescued mTORC1 inactivation induced by Aβ treatment and decreased the formation of Aβ-induced autophagosome. Conclusions We provide evidence that PRAK plays a critical role in AD pathology as a key interactor of RAGE. Thus, our data suggest that PRAK might be a potential therapeutic target of AD involved in RAGE-mediated cell signaling induced by Aβ.